CXCL13 as a Biomarker: Background and Utility in Multiple Sclerosis - Andrew R. Pachner; Steven Pike; Andrew D. Smith; Francesca Gilli (Biomolecules)
CXCL13 is a chemokine which is upregulated within the CNS in multiple sclerosis, Lyme neuroborreliosis, and other inflammatory diseases and is increasingly clinically useful as a biomarker. This review provides background for understanding its function in the immune system and its relationship to ectopic lymphoid follicles. Also reviewed are its utility in multiple sclerosis and Lyme neuroborreliosis and potential problems in its measurement. CXCL13 has the potential to be an exceptionally useful biomarker in a range of inflammatory diseases.